A Case Study Supporting Lack of SARS-CoV-2 Spread to a 3-Month Old Infant Through Exclusive Breastfeeding. (May 2021) - Liu, Wei; Liu, Yujie; Liu, Zhenjun; Hong, Changxin; Liu, Jian; Luo, Sihui; Zheng, Xueying
Introduction: During the Coronavirus Disease 2019 global pandemic, maternal and newborn wellbeing has received much attention. Detailed reports of infected women breastfeeding their infants are uncommon. Due to incomplete information available, full data about those infants' outcomes are lacking, and evidence of infectivity through breastfeeding has not been documented. Main Issue: Here, we report about a mother who breastfed her infant until she was confirmed with the SARS-Cov-2 infection. After follow-up, we have confirmed that the infant, who was breastfed by the infected mother, was not infected. Methods: A 33-year-old woman gave birth to a full-term male infant on November 8, 2019. Since birth, she had been exclusively breastfeeding the baby until she was confirmed with the SARS-Cov-2 infection on February 8, 2020. She was hospitalized, isolated from her baby, and stopped breastfeeding. Even though she remained asymptomatic, her milk was expressed using a breast pump and discarded. The mother's milk sample was collected on February 9, 2020, and the result of the nucleic acid test for COVID-19 was negative. Her infant was asymptomatic and remained virus negative. Her laboratory findings and chest Computed Tomography imaging was normal. She was treated according to the national protocol with aerosolized interferon α2β, lopinavir/ritonavir and ribavirin. Her serum SARS-CoV-2 specific antibodies(IgG and IgM) tested positive when discharged. She returned to breastfeeding after discharge. Conclusion: Our findings suggest that breastfeeding may be less of a risk than anticipated. Additional research is needed to explore this possibility.